Afirmasi positif & Relaksasi Autogenik dalam mengatasi Ketidakberdayaan pasien DM tipe II - Hartanto, Agung Eko; Elvareta, Nabella Syifa (Universitas Sultan Ageng Tirtayasa, 2024)
Diabetes Mellitus (DM) is a chronic disease that cannot be cured until now and requires sufferers to undergo long-term treatment. Prolonged physical problems experienced by people with type 2 diabetes mellitus and loss of self-control due to the absence of significant changes to heal make individuals feel helpless. Powerlessness if not overcome will lead to a psychosocial crisis that affects more severe psychiatric problems. This study aims to carry out nursing care for diabetes mellitus patients with helplessness at the South Ponorogo Health Center. This research is descriptive in the form of a case study. Powerlessness can be measured using a powerlessness questionnaire. The subject used was one respondent at the age of 54 years, suffering from type 2 diabetes mellitus since 6 years ago, moderate helplessness score, and cooperative. The results of this study showed that the main intervention was positive affirmation and autogenic relaxation therapy was performed on the first day, a score of 8 (moderate powerlessness) was obtained, while on the fourth day a score (low powerlessness) was obtained. Positive affirmation intervention and autogenic relaxation therapy is a combination that can help patients with diabetes mellitus reduce stress and improve the patient's mental well-being. The synergy of the two implementations that are carried out at each meeting, negative thoughts are changed through positive affirmations and autogenic relaxation therapy is effective in helping patients overcome the anxiety experienced by patients.